2022
DOI: 10.3390/s22114004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Room-Temperature Low-Field Magnetoresistance in Nanostructured Lanthanum Manganite Films for Magnetic Sensor Applications

Abstract: The results of colossal magnetoresistance (CMR) properties of La1-xSrxMnyO3 (LSMO) films grown by the pulsed injection MOCVD technique onto an Al2O3 substrate are presented. The grown films with different Sr (0.05 ≤ x ≤ 0.3) and Mn excess (y > 1) concentrations were nanostructured with vertically aligned column-shaped crystallites spread perpendicular to the film plane. It was found that microstructure, resistivity, and magnetoresistive properties of the films strongly depend on the strontium and manganese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…71 The linear plot of ln(ÀDS M ) vs. ln(H) at T C is depicted in Fig. 12(a) and (b), respectively, for samples L1 and L2, which in turn provides the value of n. For L1 and L2, respectively, the derived values of n are 0.748(8) and 0.797 (2). Critical exponents are established using…”
Section: Critical Exponent Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…71 The linear plot of ln(ÀDS M ) vs. ln(H) at T C is depicted in Fig. 12(a) and (b), respectively, for samples L1 and L2, which in turn provides the value of n. For L1 and L2, respectively, the derived values of n are 0.748(8) and 0.797 (2). Critical exponents are established using…”
Section: Critical Exponent Analysismentioning
confidence: 99%
“…CMR materials have attracted significant interest in recent years due to their potential application in sensors and magnetic memory devices. 2,3 Manganites have also been found to exhibit a large MCE under moderate applied fields, revealing that CMR manganites are also possible candidates for magnetic refrigeration applications. Magnetocaloric materials offer an environmentally sound and economically viable refrigeration technology as an alternative to the traditional vapour compression-expansion cycle, leading to the development of effective green cooling systems completely for both domestic and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that for single-layer polycrystalline La 0.83 Sr 0.17 Mn 1.21 O 3 films grown on quartz substrate, the LFMR at 25 K showed twice higher values (31% at 0.7 T, see Figure 7 c) in comparison to films grown on polycrystalline Al 2 O 3 or SiO 2 substrates (~15%) (see Figure 7 d,e, respectively) [ 68 ]. Recently, it was demonstrated that Mn excess ( y > 1) in polycrystalline La 1−x Sr x Mn y O 3 (LSMO) films increases the Curie temperature what results in LFMR effect at close to room temperatures [ 69 ]. It was found that the magnetoresistance of (–1.23 ÷ –0.8)% at temperatures (250 ÷ 290) K could be achieved at a magnetic field of 50 mT for La 0.7 Sr 0.3 Mn 1.15 O 3 films without the introduction of an additional insulating phase, only by the adjustment of the chemical composition and film growth conditions (see Figure 7 f).…”
Section: Colossal Magnetoresistance Materialsmentioning
confidence: 99%
“…Measurements performed at ambient temperature of 25 K. Reprinted from [ 68 ], copyright 2022 MDPI; and ( f ) MR vs. magnetic field dependences at room temperature for nanostructured La 1−x Sr x Mn y O 3 films with different Sr content x and constant Mn excess y = 1.15. Reprinted from [ 69 ], copyright 2022 MDPI.…”
Section: Figurementioning
confidence: 99%